2004
DOI: 10.1074/jbc.m405480200
|View full text |Cite
|
Sign up to set email alerts
|

Heterooligomeric Phosphoribosyl Diphosphate Synthase of Saccharomyces cerevisiae

Abstract: The yeast Saccharomyces cerevisiae contains five phosphoribosyl diphosphate (PRPP) synthase-homologous genes (PRS1-5), which specify PRPP synthase subunits 1-5. Expression of the five S. cerevisiae PRS genes individually in an Escherichia coli PRPP-less strain (⌬prs) showed that a single PRS gene product had no PRPP synthase activity. In contrast, expression of five pairwise combinations of PRS genes resulted in the formation of active PRPP synthase. These combinations were PRS1 PRS2, PRS1 PRS3, and PRS1 PRS4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This analysis furthermore showed that the simultaneous expression of PRS1 and PRS2 or the simultaneous expression of PRS1 and PRS4 resulted in PRPP synthase with very low activity in vivo, presumably too low to promote growth of S. cerevisiae Δprs3 Δprs4 Δprs5 or Δprs2 Δprs3 Δprs5 deletants. Although complementation of the E. coli Δprs allele by combinations of two PRS genes revealed the production of active PRPP synthase in vivo, in vitro PRPP synthase activity could be detected only in cell extract of the strain that expressed both PRS1 and PRS3 (82). The conclusions from this analysis are that active PRPP synthase requires either PRS1 or PRS5 in addition to at least one more PRS gene product, but not just any PRS gene product.…”
Section: Class I Prpp Synthasesmentioning
confidence: 78%
See 2 more Smart Citations
“…This analysis furthermore showed that the simultaneous expression of PRS1 and PRS2 or the simultaneous expression of PRS1 and PRS4 resulted in PRPP synthase with very low activity in vivo, presumably too low to promote growth of S. cerevisiae Δprs3 Δprs4 Δprs5 or Δprs2 Δprs3 Δprs5 deletants. Although complementation of the E. coli Δprs allele by combinations of two PRS genes revealed the production of active PRPP synthase in vivo, in vitro PRPP synthase activity could be detected only in cell extract of the strain that expressed both PRS1 and PRS3 (82). The conclusions from this analysis are that active PRPP synthase requires either PRS1 or PRS5 in addition to at least one more PRS gene product, but not just any PRS gene product.…”
Section: Class I Prpp Synthasesmentioning
confidence: 78%
“…Little is known of the enzymatic properties of S. cerevisiae PRPP synthase activity. Some activity remains following dialysis of an S. cerevisiae crude extract against P i -free buffer and in assays under P i -free conditions, and only 18% of the activity remained when the enzyme was assayed in the presence of 2 mM ADP, relative to 100% in the absence of ADP (82). These properties differ from those of bacterial PRPP synthases.…”
Section: Class I Prpp Synthasesmentioning
confidence: 89%
See 1 more Smart Citation
“…The inconsistency of this GPR was addressed in i AZ900 [ 8 ] and was modified to depict that any of the three PRS gene pairs ( PRS1 and PRS3 ), ( PRS2 and PRS5 ) or ( PRS4 and PRS5 ) is capable of encoding the sub-units required for catalyzing the reaction. However, it was later shown [ 68 ] that any of the five viable pairs (see Figure 4 ) need to be present for growth with one subunit containing an NHR (non-homologous region) and the other without one. Both PRS1 and PRS5 contain NHR while the rest do not.…”
Section: Resultsmentioning
confidence: 99%
“…PRPP is also associated with cell integrity in Saccharomyces cerevisiae [15]. The yeast genome encodes five distinct prs genes, whose products are combined to form hetero-oligomeric catalytic active PRS, with possible role in plasma membrane stability [16]. In Corynebacteriaceae, such as mycobacteria, PRPP is a co-substrate for the synthesis of polyprenylphosphate-pentoses, which are the source of arabinosyl residues of arabinogalactan, component of the mycobacterial cell wall, and lipoarabinomannan, a highly immunogenic lipoglycan that is involved in modulating the host immune response [17], [18].…”
Section: Introductionmentioning
confidence: 99%